IMF Survey, Volume 31, Issue 04. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2002)
The Group of Seven Finance Ministers and Central Bank Governors met in Canada on February 8-9 to discuss the global economy, the importance of fostering development, and ongoing efforts to combat the financing of terrorism. The Managing Director of the IMF participated in the meeting.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet